2018
DOI: 10.19080/gjo.2018.13.555860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hearing Loss and Tinnitus with Correlation to the Usage of Protective Hearing Equipment among Airport Workers

Abstract: Objectives: Epidemiological studies have shown that tinnitus and occupational hearing loss are common symptoms in the working population. Only few studies have assessed the aforementioned symptoms in this population, none of which have assessed airport field workers, thus the need for our study. Methodology:A cross-sectional study was conducted among airport field workers at King Khaled International Airport in Riyadh. The sample size was calculated to be 380. Each was asked to fill a self-administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
(18 reference statements)
1
7
1
Order By: Relevance
“…The reported prevalence of hearing loss in the present study is also high (71.6%) compared to that of other professions in Saudi Arabia such as dentists, industrial workers, and airport field workers where the prevalence ranges from 15.8% to 57%. [ 6 7 8 ] This finding correlates with the findings of other published studies about NIHL, which showed that the prevalence of hearing loss and tinnitus is higher in military personnel than in industrial workers and other professions. [ 9 25 29 ] The magnitude of the problem of hearing impairment that results from excessive noise exposure depends on several factors associated with the exposure such as sound pressure level, duration, type of noise, and frequency.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reported prevalence of hearing loss in the present study is also high (71.6%) compared to that of other professions in Saudi Arabia such as dentists, industrial workers, and airport field workers where the prevalence ranges from 15.8% to 57%. [ 6 7 8 ] This finding correlates with the findings of other published studies about NIHL, which showed that the prevalence of hearing loss and tinnitus is higher in military personnel than in industrial workers and other professions. [ 9 25 29 ] The magnitude of the problem of hearing impairment that results from excessive noise exposure depends on several factors associated with the exposure such as sound pressure level, duration, type of noise, and frequency.…”
Section: Discussionsupporting
confidence: 87%
“…[ 3 ] In Saudi Arabia, the prevalence of hearing loss of employees in noisy work environments ranges from 15.8% to 57%. [ 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…These airside workers were chosen randomly from a name list while considering shift times to cover all shifts and days of the week. The sample size was calculated using Epi Info software version 22, knowing that the total population size was n = 1948, assuming a 5% margin of error and 95% CI, and using a prevalence equal to that of the prevalence of NIHL at King Khalid International Airport in Saudi Arabia, which was found to be 48% [7]. Accordingly, the sample size was 312 participants (n = 312) after applying inclusion and exclusion criteria, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2014 Korean study, the prevalence of NIHL was 49.4% [5]. In a Sudanese study in 2008, at Khartoum International Airport, the prevalence of NIHL was 55%, and in a 2018 Saudi Arabian study at King Khalid Airport it was 48% [6,7]. Noise mapping is an important tool for evaluating and interpreting environmental noise that can provide information to concerned authorities for the mitigation of noise pollution problems such as NIHL and inform about other risk factors for NIHL among manufacturing industry workers, including noise intensity, years of service, duration of exposure, age, hypertension, risk behaviors and hearing protection device (HPD) usage [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Riyadh, measuring prevalence of hearing loss among preschoolers, the prevalence was 1.75% 3 . Prevalence of noise induced hearing impairment among airport workers in Saudi Arabia was found to be 57% 4 . Prevalence of hearing loss among elderly in Saudi Arabia was revealed to be 69% unilateral hearing loss, in which 46% were conductive, 45% sensorineural and only 9% mixed hearing loss 5 .…”
Section: Introductionmentioning
confidence: 98%